Predictive value of morphological features and proliferative markers (mitotic index, Ki-67, PHH3) in bronchopulmonary neuroendocrine tumors - L. M. Zakhartseva; H. Ye. Chytaieva (Zaporozhye State Medical University, 2021)
The aim of this study was to evaluate relations of mitotic index (MI), necrosis, IHC proliferative markers Ki-67 and PHH3, and their predictive value for lung neuroendocrine tumors (NETs) aggressiveness. Materials and methods. The study used surgical and biopsy material from 64 patients with lung NETs before chemotherapy prescribing. Morphological study and IHC was performed. MI, necrosis, Ki-67 and PHH3 expression and metastatic disease and survival were estimated using nonparametric statistics. Results. Statistically significant association of necrosis severity and survival rates was found (P = 0.021). This was true for comparing patients with no necrosis in tumor tissue and extensive foci of necrosis (P = 0.023). MI appeared to be associated with metastases in lymph nodes (P = 0.003) and with distant metastatic lesions (P = 0.029). Significant, direct association of Ki-67 and MI (P < 0.001), MI and PHH3 expression (P < 0.001) was found. However, there was no significant link between Ki-67 and PHH3 rates (P = 0.240). Ki-67 didn't show any significant association with necrosis and metastases. Also, Ki-67 rates didn't affect the patient survival. Data on PHH3 expression and their estimation appeared to be rather contradictory. PHH3 expression rates were lower than expected and did not exceed neither Ki-67 rates, nor MI. Conclusions. MI and necrosis are reliable markers for the assessment of lung NETs aggressiveness. MI is statistically associated with metastatic lesion, while extensive necrosis - with survival rates. Ki-67 expression was significantly associated with MI. No significant association of Ki-67 and PHH3 expression, tumor's morphological features, disease progression and prognosis was found. Contrary to our expectations, PHH3 showed no diagnostic and prognostic value in lung NETs.